ANALYSIS OF THE DIGITALIZATION OF POPULATION ADMINISTRATION SERVICES ON REGIONAL DEVELOPMENT PLANNING THROUGH THE USE OF POPULATION DATA SYSTEM - Adisti Maritadinda Admar; Sirojuzilam; Badaruddin; Rujiman (Universitas Efarina, 2022)
The impact of the ongoing digitization of population administration services on regional development planning through the population utilization system is expected to become a common ground for closing various gaps in efforts to optimize data utilization. This gap is the focus of the study so that improvements can be made in the future. This study examines from various sides, starting from recording and documentation, data publication, data development, data utilization, ease of use of data, quality of data information, to the reliability of data administration. In addition, we also tried to dig deeper into the respondents' knowledge of population information systems, user data needs, and what data can be collaborated between agencies. Utilization of population data that is easy and valid is needed in an effort to accelerate regional development performance in solving various urgent problems at hand and in the long term. Valid planning cannot be presented if the data used in planning is not valid. Planning that responds quickly to changes in social conditions is difficult to realize if there is no ease in terms of data access. The validity of the data in question is not only talking about the suitability of recorded population events with the actual situation, but also how the recorded data is able to describe the actual number. Up to this point, the ease of access to data for users to be used in relation to their field of work is expected to give rise to higher quality planning. The Medan City Population and Civil Registration Service as the implementing agency in charge of population administration affairs has taken a step forward in building a digital-based population data system. Efforts to optimize performance are continuing, and this study is an endeavor that is expected to add energy to population administration administrators in supporting the established vision and mission of Medan City.